Uji Aktivitas Antidiabetes dari Ekstrak Daun Salam (Syzygium polyanthum) Menggunakan Metode Inhibisi Enzim α-Amilase Secara In Vitro - Devi Nur Indah Sari; Kharisma Jayak P; Tatiana Siska Wardani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Diabetes Mellitus is a metabolic disorder caused by the pancreas failing to produce insulin hormone adequately. Based on the cause, diabetes mellitus is classified into three types, including type 1 DM, type 2 Diabetes Mellitus, and gestational diabetes mellitus. Hyperglycemia can also occur due to food consumed that is not balanced with physical activity carried out so that fat accumulates in the body and causes blood to be unable to enter the body's cells, ultimately increasing blood sugar levels. Signs and symptoms that often appear in Diabetes Mellitus patients are polydipsia (excessive thirst), polyuria (frequent urination due to excessive urine production), polyphagia (quickly feeling hungry even though you eat a lot and want to eat continuously) and weight loss without a clear cause. Symptoms of diabetes mellitus can be controlled by increasing physical activity, following a healthy diet, and getting enough rest. Several studies have proven that bay leaves have the potential as an antidiabetic. This study aims to determine the content of secondary metabolic compounds and the antidiabetic activity of bay leaf extract using α-amylase enzyme inhibition in vitro. This research method uses laboratory experiments. This study uses α-amylase enzyme inhibition to determine the antidiabetic activity contained in bay leaf extract. The method used is DNSA. The results of this study obtained a yield of bay leaf extract of 30%, water content of simplicia of 6.24%, drying loss of simplicia of 5.3%, ash content test of 5.6%, water content test of extract of 6.34%, drying loss test of extract of 7.03%. Bay leaf extract positively contains secondary metabolite compounds, namely saponins, tannins, flavonoids, and alkaloids. The results of IC50 in bay leaf extract of 66.705 ppm are classified as strong antidiabetic. The results of acarbose of 56.818 ppm are classified as strong antidiabetic.